Semisolid Fermentation of Ryegrass Straw - Han, Y. W. (1975)
Candida utilis, Aureobasidium pullulans, and Trichoderma viride were grown on pretreated ryegrass straw. The pretreatment consisted of hydrolysis of straw with 0.5 N H(2)SO(4) (water-substrate, 3:1) at 121 C, 100 C, and room temperature and adjustment of the hydrolysate to pH 4.5 to 5.0 with 5 N NH(4)OH. The 121 C pretreatment yielded a material containing 30% sugar and 2.3% N. The fermentation was carried on semisolid substrate (moisture level, 75%) in rotating jars for 2 to 3 days at room temperature. The organisms grew rapidly during the period from 18 to 42 h of incubation. During this period the number of microbial cells increased by 20- to 200-fold, and the level of NH(3)-N decreased from 1.3 to 0.9%. The fermentation resulted in a fourfold increase in protein, fivefold increase in crude fat, and 40% increase in the digestibility of straw. The best result in terms of increasing protein and digestibility of straw was obtained when C. utilis was grown on straw preheated at 121 C.